ABT-263 exerts a protective effect on upper urinary tract damage by alleviating neurogenic bladder fibrosis - Yibo Wen; Junwei Wu; Qingsong Pu; Xiangfei He; Junkui Wang; Jinjin Feng; Yanping Zhang; Feng Si; Jian Guo Wen; Jinghua Yang (Renal Failure)
This study investigated the mechanism of action of ABT-263 in the treatment of neurogenic bladder fibrosis (NBF)and its protective effects against upper urinary tract damage (UUTD). Sixty 12-week-old Sprague-Dawley (SD) rats were randomly divided into sham, sham + ABT-263 (50 mg/kg), NBF, NBF + ABT-263 (25 mg/kg, oral gavage), and NBF + ABT-263 (50 mg/kg, oral gavage) groups. After cystometry, bladder and kidney tissue samples were collected for hematoxylin and eosin (HE), Masson, and Sirius red staining, and Western Blotting (WB) and qPCR detection. Primary rat bladder fibroblasts were isolated, extracted, and cultured. After co-stimulation with TGF-β1 (10 ng/mL) and ABT-263 (concentrations of 0, 0.1, 1, 10, and 100 µmol/L) for 24 h, cells were collected. Cell apoptosis was detected using CCK8, WB, immunofluorescence, and annexin/PI assays. Compared with the sham group, there was no significant difference in any physical parameters in the sham + ABT-263 (50 mg/kg) group. Compared with the NBF group, most of the markers involved in fibrosis were improved in the NBF + ABT-263 (25 mg/kg) and NBF + ABT-263 (50 mg/kg) groups, while the NBF + ABT-263 (50 mg/kg) group showed a significant improvement. When the concentration of ABT-263 was increased to 10 µmol/L, the apoptosis rate of primary bladder fibroblasts increased, and the expression of the anti-apoptotic protein BCL-xL began to decrease.ABT-263 plays an important role in relieving NBF and protecting against UUTD, which may be due to the promotion of myofibroblast apoptosis through the mitochondrial apoptosis pathway.